Financial AIDS among ASNAf in private higher education institution in Malaysia - Mat Isa A.A.; Talib M.H.; Abdul Rahman E.Z.E. (Mattingley Publishing, 2023)
Education; Mechanical engineering; Test facilities; Asnaf; Conceptual study; Financial aids; Financial sustainability; Hard cores; Higher education institutions; Private educations; Zakat; Finance